Ecology and conservation of the Snow Leopard (Panthera uncia) in the Pamir Mountain Range, Central Asia / Jaffar Ud Din - Jaffar , Ud Din (2023)
The snow leopard (Panthera uncia) is a vulnerable umbrella species that thrives in the mountains of Central and Southeast Asia. Its population is declining globally due to both conventional and emerging threats. Despite the iconic status of the species and the enormous importance of its ecosystems, knowledge gaps in relation to species ecology and management are widely acknowledged. This study investigated snow leopard ecology in the transborder region of the Pamir and recognized conservation measures based on the knowledge gained on snow leopard ecology, conflicts with humans, and the economic potentials of the ecosystem services. Sign-based site occupancy surveys conducted from 2010-2012 across a 2,725 km² area confirmed the presence of snow leopards across the Pamir-Karakoram mountains. Occupancy was the highest in Khunjerab National Park (ψ = 0.57 ± 0.03) followed by Qurumbar National Park (ψ = 0.46 ± 0.05), the Misgar-Chipursan valleys (ψ = 0.42 ± 0.03), and Broghil National Park (ψ = 0.35 ± 0.04). The presence of predators, such as snow leopards, means inevitable conflicts with the pastoralist communities. The questionnaire surveys of 182 agropastoral households conducted in 2013 revealed an explicit seasonal and spatial variation in livestock depredation in the transborder region. Predation incidences were higher in the evening, and sheep and goats accounted for 92% of offtake. Overall, 315 heads of livestock were reportedly killed by snow leopards (47%) and wolves (53%) in the study sites, per year. This serious livestock loss was further aggregated by the disease-caused mortality, which was even imparted two-fold damage of the predation. The collective economic burden of predation and diseases was US$543 per household per year, which explains the low public tolerance for predators in the region. The low public acceptance of the predators triggered poaching and facilitated trade in snow leopards. An investigation of the dynamics of poaching and trade in snow leopards in Pakistan revealed that a total of 101 snow leopards were killed and traded during 2005–2017. Reported poaching incidents varied spatially (x̅ = 9 ± 2.6 [95% Cl: 3–15]) and temporally (x̅ =7.8 ± 1.09) and accounted for a 2–4% annual population loss (n = 200–420) over 13 years. The average base and end prices for each pelt were US$ 245 ± 36 and US$ 1,736 ± 520, respectively. The ecosystems inhabited by snow leopards are of immense value for the survival of millions of human beings. The economic worth of ecosystem services assessed in Khunjerab and Qurumbar national parks measured at US$ 4.6 million and US$ 3.8 million annually, which translates into US$ 5955 and US$ 8912 per household per year. The findings of this study underpin improved management of protected areas to ensure the protection of wildlife in the study sites. Moreover, tangible conservation measures to offset predator-induced economic losses and the development of a multi-stakeholder coordination mechanism to curb poaching and trade in wildlife are essential. The worth of the ecosystem services should also be considered in future planning and investments in these landscapes.